2020
DOI: 10.3390/su13010166
|View full text |Cite
|
Sign up to set email alerts
|

Governmental Intervention and Its Impact on Growth, Economic Development, and Technology in OECD Countries

Abstract: The governments’ intervention in the economy impacts technological performance and sustainability. This role has become even more critical due to the COVID-19 situation and in the context of the continuous increase in resource consumption, which requires finding alternative solutions. We provide a comprehensive literature review about the state’s economic functions, redistribution of resources in society, and the role of state intervention in sustainability-related issues, giving a full description of the opin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…The major problem faced by the global economy in 2020 was the COVID-19 pandemic. Its impact has been seen not only in the sphere of healthcare [1], but it has also affected the economic growth, the business model of companies [2,3], the need for government aid programs, as well as the condition of public finances [4]. As Çetin and Kara [5] point out, while from the perspective of public finances, pandemic diseases can only cause short-term fiscal shocks, from the point of view of economic growth, the impact will be long-term.…”
Section: Introductionmentioning
confidence: 99%
“…The major problem faced by the global economy in 2020 was the COVID-19 pandemic. Its impact has been seen not only in the sphere of healthcare [1], but it has also affected the economic growth, the business model of companies [2,3], the need for government aid programs, as well as the condition of public finances [4]. As Çetin and Kara [5] point out, while from the perspective of public finances, pandemic diseases can only cause short-term fiscal shocks, from the point of view of economic growth, the impact will be long-term.…”
Section: Introductionmentioning
confidence: 99%
“…Ref. [20] highlighted that expenditures on education may lead to better technological outcomes, unlike expenses on health. The tax burden inhibits innovation and technological progress, but total governmental revenues positively affect technological performance.…”
Section: Introductionmentioning
confidence: 99%
“…According to [17], financial markets are thought to have bad performance because of COVID-19. As a result, most governments in developed and developing countries imposed a set of actions and formulated many decisive decisions to mitigate the consequences of the pandemic on economies [14,21,26,[34][35][36][37][38]. [35] found that increasing the government expenses in general and on education in particular, will make the whole economy have better technological results for the economy.…”
Section: Covid-19 and Stock Market Indicesmentioning
confidence: 99%